Comparative study on microbiological and histopathological examination of diabetic wounds managed by conventional dressing and vacuum assisted closure therapy - Kumar, P. Ganesh; Raja, K.; Haritha, P.; Saravanakumari, A. D.; Shanthi, D.; Vasanthi, S. (International Surgery Journal, 2021)
Background: Diabetes mellitus and its complications are rising. Managing the diabetic foot wound is very challenging. Early intervention and intense management using modern technique will improve the diabetic wounds for a definitive procedure and also prevent, reduce the level of amputation of extremity. Our study compares the microbiological and histopathological results of diabetic wounds managed by conventional dressing and VAC (vacuum assisted closure) therapy. Methods: This was an institutional based prospective study conducted between July 2018 and July 2019 consisting of 50 patients with diabetic wound of lower extremities. Patients were divided into group A- 25 patients underwent conventional dressing and group B- 25 patients underwent negative pressure wound therapy (NPWT). Wound swab and tissue biopsy was obtained on day 0 and day 10 from both groups and compared. Results: Among patients, 76% and 24% were males and females respectively. Histopathologically, necrosis and inflammatory cell infiltrate were significantly decreased in group B compared to group A. Angiogenesis increased notably in group B. On microbiological grounds, from both groups Pseudomonas aeruginosa was found to be the most common organism on day 0 and 10. But the prevalence of infection in group B was grossly reduced when compared to group A. Conclusions: VAC therapy is a better modality to treat diabetic wound compared to conventional dressing as it accelerates the healing of a chronic wound by increasing angiogenesis and decreasing necrosis, inflammatory cell infiltrate and microbial growth.